Pengaruh massage endorphin dan aroma terapi chamomile terhadap kecemasan ibu hamil trimester III - Jenny Kartika; Nia Clarasari Mahalia Putri (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Anxiety in pregnant women is a psychological problem that continues when facing childbirth, causing difficulty and duration of labor and will be at risk of maternal death. In general, anxiety disorders are characterized by excessive fear and anxiety, as well as certain behavioral disorders. Endorphin massage is one way to reduce anxiety by eliminating fatigue in the body and creating a sense of comfort. Purpose: To determine the effect of endorphin massage and chamomile aromatherapy on anxiety levels in pregnant women in the third trimester. Method: Quantitative quasi-experimental research using purposive sampling technique. The independent variables consist of aromatherapy and endorphin massage, while the dependent variable is the level of anxiety of pregnant women. Data were analyzed using univariate and bivariate Chi Square tests. Results: Participants who were not given aromatherapy experienced anxiety as many as 23 participants (51.1%) and for participants who were given aromatherapy, most did not experience anxiety as many as 42 participants (82.4%). The results of statistical analysis with the chi square test obtained a value of ρ = ​​0.001 and an OR value of 4.879, meaning that 4.879 times more likely to experience anxiety disorders for those who were not given aromatherapy. The level of anxiety of pregnant women who were not given endorphin massage was also higher as many as 33 participants (73.3%), while pregnant women who were given endorphin massage did not experience anxiety as many as 46 participants (90.2%). The results of statistical analysis with the chi-square test showed a ρ value of 0.000, this indicates that there is a relationship between the level of anxiety of pregnant women and the provision of endorphin massage. Based on the OR value, pregnant women who are not given endorphin massage are 25.3 times more likely to experience anxiety disorders. Conclusion: The provision of aromatherapy and endorphin massage has an effect on reducing anxiety levels in pregnant women in the third trimester. Suggestion: It is expected that the provision of aromatherapy and endorphin massage can continue to be used as an alternative therapy to reduce anxiety levels in pregnant women. It is expected to provide information to pregnant women about aromatherapy and endorphin massage as non-pharmacological therapies in reducing anxiety levels in pregnant women, it is expected that further researchers can conduct research with other variables that have not been studied. Keywords: Anxiety; Aromatherapy; Endorphin Massage; Pregnant Women. Pendahuluan: Kecemasan ibu hamil merupakan permasalahan psikologis yang berlanjut saat menghadapi persalinan, sehingGa menimbulkan kesulitan dan lamanya persalinan serta akan berisiko pada kematian ibu. Secara umum, gangguan kecemasan memiliki ciri-ciri ketakutan dan kecemasan yang berlebihan, serta gangguan perilaku tertentu. Massage endorphin merupakan salah satu cara untuk menurunkan kecemasan dengan cara menghilangkan rasa lelah pada tubuh dan menciptakan rasa nyaman. Tujuan: Untuk mengetahui pengaruh massage endorphin dan aroma terapi chamomile terhadap tingkat kecemasan ibu hamil trimester III. Metode: Penelitian kuantitatif quasi experimental menggunakan teknik pengambilan sampel purposive sampling. Variabel independen terdiri dari aroma terapi dan massage endorphin, sedangkan variabel dependen yaitu tingkat kecemasan ibu hamil. Data dianalisis menggunakan univariat dan bivariat uji Chi Square. Hasil: Partisipan yang tidak diberi aroma terapi mengalami kecemasan sebesar 23 partisipan (51.1%) dan bagi partisipan yang diberikan aroma terapi sebagian besar tidak mengalami kecemasan sebanyak 42 (82.4%). Hasil analisis statistik dengan uji chi-square ρ value = 0.001 dan nilai OR 4.879, artinya 4.879 kali lebih besar kemungkinan mengalami gangguan kecemasan bagi yang tidak diberikan aroma terapi. Tingkat kecemasan ibu hamil yang tidak diberi massage endorphin juga lebih tinggi sebanyak 33 partisipan (73.3%), sedangkan ibu hamil yang diberikan massage endorphin lebih banyak tidak mengalami kecemasan sebanyak 46 partisipan (90.2%). Hasil analisis statistik dengan uji chi-square menunjukkan ρ value sebesar 0.000, hal ini menunjukkan ada korelasi antara tingkat kecemasan ibu hamil dan pemberian massage endorphin. Menurut nilai OR yang ibu hamil yang tidak diberi massage endorphin 25.3 kali lebih besar kemungkinan mengalami gangguan kecemasan. Simpulan: Pemberian aroma terapi dan massage endorphin berpengaruh pada penurunan tingkat kecemasan ibu hamil trimester III. Saran: Diharapkan pemberian aroma terapi dan massage endorphin ini dapat terus dimanfaatkan sebagai salah satu terapi alternatif untuk mengurangi tingkat kecemasan ibu hamil. Diharapkan dapat memberikan informasi kepada ibu hamil tentang aroma terapi dan massage endorphin sebagai terapi non farmakologis dalam menurunkan tingkat kecemasan ibu hamil, diharapkan untuk peneliti selanjutnya agar dapat meneliti dengan variabel lainnya yang belum diteliti. Kata Kunci: Aroma Therapy; Ibu Hamil; Kecemasan; Massage Endorphin.